Newborn Health and the Business Cycle: Is it Good to be born in Bad Times? - Ainhoa Aparicio (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2014)
We study the effect of the cycle on the health of newborn babies using 30 years of birth-certificate data for Spain. We find that babies are born healthier when the local unemployment rate is high. Although fertility is lower during recessions, the effect on health is not the result of selection, since the main result survives the inclusion of parents' fixed-effects. Analysis of National Health Survey data shows that fertility-age women engage in healthier behaviors during recessions (in terms of exercise, sleep, smoking and drinking) and report better overall health. We conclude that maternal health is a plausible mediating channel.
Keywords: E32; I10; J13; 330